Kirkebjerget: A Late Bronze Age Settlement at Voldtofte, South-West Funen - Berglund, Joel (Journal of Danish Archaeology, 1982)
Kirkebjerget- A Late Bronze Age Settlement at Voldtofte, South-West Funen